2020
DOI: 10.21203/rs.3.rs-57627/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural insights into spike protein and its natural variants of SARS-CoV-2 found on Mexican population.

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a newly emerged coronavirus responsible for COVID-19; it becomes a pandemic since March 2020. To date, there are described three lineages of SARS-CoV-2 circulating worldwide, in Mexican population are found two of them, within this, we observed three variants of Spike (S) protein located at H49Y, D614G, and T573I. In order to understand if these mutations could affect the structural behavior of S protein of SARS-CoV-2, as well as the binding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(58 reference statements)
1
1
0
Order By: Relevance
“…This analysis indicates that only S-protein WT exhibited high flexibility of residues (residues 331–504) involved in forming the RBD (residues 319–541), indicating that both mutations contributed to a decrease in mobility at this region involved in the molecular recognition. This lower mobility at RBD for mutants may be responsible for the differences in affinity for potential S-protein inhibitors as previously reported [ 23 ]. For free ACE2, it was observed that high mobility was localized along with residues 71–86, 146–186, 246–266, 330–370, 404–431, 447–470, 471–505, and 557–587 ( Fig.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This analysis indicates that only S-protein WT exhibited high flexibility of residues (residues 331–504) involved in forming the RBD (residues 319–541), indicating that both mutations contributed to a decrease in mobility at this region involved in the molecular recognition. This lower mobility at RBD for mutants may be responsible for the differences in affinity for potential S-protein inhibitors as previously reported [ 23 ]. For free ACE2, it was observed that high mobility was localized along with residues 71–86, 146–186, 246–266, 330–370, 404–431, 447–470, 471–505, and 557–587 ( Fig.…”
Section: Resultssupporting
confidence: 58%
“…To date, the major mutations detected worldwide have been localized on the viral S-protein [ [18] , [19] , [20] , [21] ]; in the Mexican population, two of three viral lineages have been reported [ 22 ], however, structural insight into how these mutations impact the S-protein of SARS-CoV-2 and its molecular recognition of ACE2 is still missing. In a recent computational study, it was identified that H49Y, D614G, and T573I mutations in the Mexican population differently impact the affinity of some potential inhibitors of the S-protein [ 23 ]. In addition, it has been reported that the H49Y mutation is linked to a reduction in total free energy, while the D614G substitution has a more stabilizing effect [ 21 ].…”
Section: Introductionmentioning
confidence: 99%